2013
DOI: 10.21608/jacb.2013.53217
|View full text |Cite
|
Sign up to set email alerts
|

ESTIMATING THE GENETIC PARAMETERS OF YIELD AND YIELD COMPONENT TRAITS IN SQUASH (Cucurbita pepo, L.)

Abstract: The main objective of this investigation was to determine the genetic parameters, heritability in both broad and narrow senses, combining abilities and correlation for yield and yield component traits in squash (Cucurbita pepo, L.). For this purpose, five squash varieties were used .These varieties were: Eskandrani (P1); Zucchino tondo di piacenza (P2); Black beouty (P3); Zucchino romanesco (P4) and Coppi (P5). During the summer season of 2011, acomplete diallel crosses mating design was made to evaluate the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 2 publications
3
6
0
Order By: Relevance
“…P 1 , P 2 and P 4 seemed to be the best combiners for F.Y./P.kg. These results were in agreement with the results obtained by Abd El-Hadi et al, (2004); Abdein (2005); Al-Ballat 2008; Pradip et al, (2013) and Sanin et al, (2014).…”
Section: General Combining Ability Effects (G I ) For the Parentssupporting
confidence: 93%
See 3 more Smart Citations
“…P 1 , P 2 and P 4 seemed to be the best combiners for F.Y./P.kg. These results were in agreement with the results obtained by Abd El-Hadi et al, (2004); Abdein (2005); Al-Ballat 2008; Pradip et al, (2013) and Sanin et al, (2014).…”
Section: General Combining Ability Effects (G I ) For the Parentssupporting
confidence: 93%
“…These results were in agreement with the results obtained by Abd El-Hadi et al, (2001); Abd El-Hadi et al, (2004); Iathet and Piluek (2006); Al-Araby, (2010); Thangamani, et al, (2011); Jahan et al, (2012) and Marie et al, (2012).…”
Section: Heterosis For Better Parent (H Bp %):-supporting
confidence: 92%
See 2 more Smart Citations
“…The results also showed that the degrees of heterosis vs. mid parents had really significant values for the majority of the variables studied, and the projections of heterosis vs. the better parent were highly significant for the majority of the variables studied. Although some hybrids showed significant heterosis for some variables, none of the hybrids demonstrated increased heterosis for all variables and preferable heterosis over the mid and better parents [162]. Heterosis breeding allows for a one-generation enhancement in yield and other desirable traits that would be more time consuming and difficult to achieve with other traditional breeding procedures [163].…”
Section: Evaluation Of Heterosis or Hybrid Vigormentioning
confidence: 98%